Usulan Perbaikan Kualitas Pelayanan Dengan Menggunakan Metode Gap Analysis & Kano Model Pada Menstilo Barbershop - RAFIF, FAISHAL HAMMADI; MUKTI, YOANITA YUNIATI (e-Proceeding FTI, 2024)
Many changes and rapid advances in the field of business and service industries make people increasingly concerned with business development. In business development, it is necessary to pay attention to the quality aspect. Based on the problem, Menstilo Barbershop received several complaints about the quality of its services such as the lack of available parking space, uncomfortable places, shampooing places that are limited to only a few, and others. The purpose of this study is to produce proposed improvements to Menstilo Barbershop to improve service quality performance and reduce complaints so as to increase customer satisfaction with the Gap Analysis method and Kano Model. Data collection was carried out by distributing questionnaires through google form to 100 respondents. The test results show that in the Gap Analysis method there are 25 service attributes that have satisfied consumers and there are 6 service attributes that have not satisfied consumers. Kano Model data processing, classifies attributes into 3 categories, namely Must-be (1 attribute), One-Dimensional (29 attributes), and Attractive (1 attribute ). From the results of the comparison, LA Barbershop was found as Menstilo's main competitor. Based on integration between Gap Analysis and Kano Model, the improvement process is carried out on 6 attributes that have not met expectations and sorted by Kano Model this producing proposals for improvements to service attributes in accordance with the priority order of improvement based on the integration of Gap Analysis and Kano Models. Abstrak Banyaknya perubahan dan kemajuan pesat di bidang industri bisnis dan jasa membuat masyarakat semakin mementingkan perkembangan bisnis. Dalam pengembangan bisnis, perlu memperhatikan aspek kualitas. Berdasarkan permasalahan, Menstilo Barbershop menerima beberapa komplain mengenai kualitas layanannya seperti kurangnya lahan parkir yang tersedia, tempat yang kurang nyaman, tempat keramas yang terbatas hanya beberapa, dan lain – lain. Tujuan penelitian ini adalah menghasilkan usulan perbaikan pada Menstilo Barbershop untuk memperbaiki performansi kualitas pelayanan dan mengurangi komplain sehingga meningkatkan kepuasan konsumen dengan metode Gap Analysis dan Kano Model. Pengumpulan data dilakukan dengan menyebarkan kuesioner melalui google form kepada 100 responden. Hasil pengujian menunjukan bahwa pada metode Gap Analysis terdapat 25 atribut pelayanan yang telah memuaskan konsumen dan terdapat 6 atribut pelayanan yang belum memuaskan konsumen. Pengolahan data Kano Model, mengklasifikasikan atribut ke 3 kategori, yaitu Must-be (1 atribut), One-Dimensional (29 atribut), dan Attractive (1 atribut). Dari hasil perbandingan maka didapatkan LA Barbershop sebagai pesaing utama Menstilo. Berdasarkan integrasi antara Gap Analysis dan Kano Model, proses perbaikan dilakukan pada 6 atribut yang belum memenuhi ekspektasi dan diurutkan dengan Kano Model sehingga menghasilkan usulan perbaikan terhadap atribut pelayanan sesuai dengan urutan prioritas perbaikan berdasarkan integrasi Gap Analysis dan Kano Model.